A Proposed Big Data as a Service (BDaaS) Model - Mazin S, Al Hakeem (International Journal of Computer Sciences and Engineering, 2025)
Big Data can bring big benefits for all sectors of our life via smarter moves, for examples, by analyzing huge dataset immediately and allowing for making decisions based on what they have learned, by gauging customer needs immediately and analyzing customer satisfaction in a timely manner, or by providing many diagnosis or treatment options quickly. These can driving business and economy growth. Until recently, it was hard to get benefits of Big Data without heavy infrastructure investments; for that, the enterprises suffered from many challenges which related to the lack of capacity to process and store the huge dataset adequately, and inability to manage and extract value from these huge dataset; but times have changed. The technology of cloud computing was evolved rapidly to bridge the storage and processing gap and opened up a lot of options for using Big Data by both individuals and organizations without having to invest in massive on-site storage and data processing facilities. This paper presents the concept, advantages, characteristics, processing and applications of Big Data. Then proposes a model to integrate Big Data and cloud computing technology based on three basic cloud service layers to present a new model of Big Data as a Service (BDaaS). The proposed BDaaS model allows enterprise to implement various Big Data functions using variety outsourcing (like Hadoop, Altiscale and Qubole) clearly, easily and moving them out of the expensive whirlpool of updating and maintaining their infrastructure.